2021
DOI: 10.1101/2021.08.04.454762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific telomere protection ensured by FOXO3a upon genotoxic stress and during aging

Abstract: Longevity is determined by diverse signaling pathways including telomere protection and homeostasis master regulators like FOXO3a. We previously showed that the telomeric repeat binding factor 2 (TRF2) expression decreases with age in human skeletal muscle and that, surprisingly, its loss in myofibers does not trigger telomere deprotection. We reveal here that in TERF2-compromised myotubes, FOXO3a is recruited to telomeres where it acts as a protective factor against ATM-dependent DNA damage activation. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Longevity is also associated with other signaling pathways related to telomere protection, like the homeostasis master regulator FOXO3. A recent study demonstrated a direct connection between FOXO3 and telomere protection, highlighting an unexpectedly higher level of integration in the regulation of the longevity signaling pathway [ 141 ].…”
Section: Potential (Poly)phenol Targets In Senescent and Cancer Cellsmentioning
confidence: 99%
“…Longevity is also associated with other signaling pathways related to telomere protection, like the homeostasis master regulator FOXO3. A recent study demonstrated a direct connection between FOXO3 and telomere protection, highlighting an unexpectedly higher level of integration in the regulation of the longevity signaling pathway [ 141 ].…”
Section: Potential (Poly)phenol Targets In Senescent and Cancer Cellsmentioning
confidence: 99%